2021
DOI: 10.1007/s12369-021-00766-w
|View full text |Cite
|
Sign up to set email alerts
|

What if Social Robots Look for Productive Engagement?

Abstract: In educational HRI, it is generally believed that a robots behavior has a direct effect on the engagement of a user with the robot, the task at hand and also their partner in case of a collaborative activity. Increasing this engagement is then held responsible for increased learning and productivity. The state of the art usually investigates the relationship between the behaviors of the robot and the engagement state of the user while assuming a linear relationship between engagement and the end goal: learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…Further, we refer to multi-modality as the application and interplay of multiple semiotic modes in order to help understand a specific process, in this case, learning. In previous work (Nasir, Bruno, et al, 2021a), we found that in an open-ended collaborative learning activity, multimodal behaviors (extracted from video, audio, and log data) better distinguish those who learn from those who do not compared to when only a single modality was used. Further, we argue that it is not straightforward to classify a certain behavior as absolutely good or bad for learning.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Further, we refer to multi-modality as the application and interplay of multiple semiotic modes in order to help understand a specific process, in this case, learning. In previous work (Nasir, Bruno, et al, 2021a), we found that in an open-ended collaborative learning activity, multimodal behaviors (extracted from video, audio, and log data) better distinguish those who learn from those who do not compared to when only a single modality was used. Further, we argue that it is not straightforward to classify a certain behavior as absolutely good or bad for learning.…”
Section: Introductionmentioning
confidence: 88%
“…This dataset, with multi-modal behaviors as well as performance metrics and learning gains, has been made publicly available (Nasir, Bruno, et al, 2021a). It must be noted that, in our dataset, all behaviors are treated as cross-sectional averages and frequencies (i.e., over the entire duration of the task), and thus it is not time series data.…”
Section: Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…At a higher level, lack of understanding/learning etc. could be reflected by other phenomena (such as other multimodal features (Nasir et al, 2020a(Nasir et al, , 2021), other expressions ("I don't understand") etc. Since there are many ways to learn, and hence different behaviours that could result in learning, it is unsurprising that such patterns are difficult to capture.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study [23], a post-intervention analysis on multi-modal data collected during learning activities involving a humanoid robot and two children was presented. The authors extracted engagement-related features from video, audio and log data in order to establish correspondences between clustered pairs of students and their corresponding behavior patterns and learning labels.…”
Section: Introductionmentioning
confidence: 99%